Complicated Onodi cell mucocele presenting with orbital apex syndrome; a case report and literature review - Akbari Dilmaghani, Nader; Sharifi, Guive; Arastou, Shima (Journal of Otorhinolaryngology and Facial Plastic Surgery, 2018)
Mucocele is defined as the accumulation of mucus within a cystic structure lined by mucoperiosteum causing bone remodeling and erosion. The sphenoidal sinus mucoceles, due to its proximity to the optic nerve, can cause ocular complications. A50-year-old woman with a history of previous endoscopic nasal surgery (30 months ago), blurred vision, severe right-sided orbital pain since three weeks ago and severe unilateral headache was admitted. Mucocele related orbital apex syndrome due to the sphenoid sinus mucocele was diagnosed. The optic nerve was fully dehiscent and under compression. Paranasal sinus pathologies must be taken into consideration when a patient with the diagnosis of optic neuropathy and involvement of the superior orbital fissure is approached.